Theories of Tiredness in Sport - Dragan Krivokapić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
Classic theories interpret the phenomena of tiredness as a consequence of biochemical changes appearing in the whole organism or in active organs. From operational point of view we can define tiredness as a reversible psychophysical condition appearing under the influence of expanded time of activities, which is manifested a series of negative changes on physiological, psychological and behavioral plan. Physiological nature was primarily related by the scientists to lack of oxygen and other nutritional material in blood or blood plasma andloading of different waste material and metabolism products On those bases, three classical theories were founded, such as: theory of suffocation, theory of exhaustion, and theory of saturation, united in one general name as hormonal theories of tiredness. Lately, with extending of findings on the role of reticular formation, there are activation theories of tiredness being developed. Supporters of these theories have discovered a series of complex connections and relations existing through tiredness and different forms of brain work such as: exhaustion of neural cells during their activity, neural influences determining arrival of nutritious material into work active organs, disruption of harmony in neurophysiological processes, role of inhibition process etc. For explanation of mental tiredness, central brain theory of tiredness is dominantly used. Due to new findings of neurophysiology, a neurophysiological theory known as theory of changed hronaxy, starting from time constant of skeletal nerve irritability, is nowadays commonly used for explanation of physical tiredness at skeletal muscles.